Strategy Management In Overcoming Religion Conflicts In Plural Communities In Mopuya Selatan Village, Bolaang Mongondow District - Dian Adi Perdana; Budi Nurhamidin (Islam Realitas: Journal of Islamic and Social Studies, 2021)
This research aims to discuss the pluralism in heterogeneous region that focuses on three communities of different religions living side by side in harmony and peace. The Plural community develops in South Mopuya Village makes the prevention of conflict needs to be improved.. Researcher discusses how the strategies of religious leaders does and government give understanding to Mopuya’s society to avoid and prevent conflict in plural society. This research is using qualitative method. The data are gained by using some techniques such as observation, interviews, and documentation. Data obtained will be analyzed using qualitative descriptive analysis. Plurality in this study, assimilation of activities, Need each other at work and increasing awareness of the importance of education, tabligh da’wah and worship tolerance are strategies to prevent conflict. Persuasive approach and language equality as unifying solution for a plural society to live in harmony and peace. Masyarakat Plural berkembang di Desa Mopuya Selatan menjadikan pencegahan konflik antar umat beragama perlu ditingkatkan. Peneliti akan mengkaji pluralisme di wilayah heterogen yang terfokus pada keagamaan dengan tiga komunitas penganut agama yang berbeda hidup berdampingan dengan rukun dan damai. Penelitian ini mengkaji bagaimana strategi tokoh agama dan pemerintah dalam memberikan pemahaman kepada umatnya untuk menghindari dan mencegah konflik pada masyarakat plural dan bagaimana tantangan serta solusi tokoh lintas agama dalam mengatasi konflik pada masyarakat plural. Penelitian ini merupakan penelitian kualitatif dengan teknik pengumpulan data observasi, wawancara dan dokumentasi Data yang diperoleh akan dianalisis menggunakan analisis deskriptif kualitatif. Pluralitas dalam studi ini, asimilasi kegiatan, saling membutuhkan dalam pekerjaan dan meningkatkan kesadaran akan pentingnya pendidikan, dakwah tabligh dan toleransi ibadah menjadi strategi mencegah konflik. Pendekatan persuasif dan penyetaraan bahasa sebagai solusi pemersatu masyarakat plural untuk hidup rukun dan damai.